Functional Quality, Mineral Composition and Biomass Production in Hydroponic Spiny Chicory (Cichorium spinosum L.) Are Modulated Interactively by Ecotype, Salinity and Nitrogen Supply - Chatzigianni, Martina; Ntatsi, Georgia; Theodorou, Maria; Stamatakis, Aristidis; Livieratos, Ioannis; Rouphael, Youssef; Savvas, Dimitrios (Frontiers in Plant Science, 2019)
The hydroponic cultivation of spiny chicory (Cichorium spinosum L.), also known as stamnagathi, allows the development of year-round production. In the current study, two contrasting stamnagathi ecotypes originating from a montane and a coastal-marine habitat were supplied with nutrient solution containing 4 or 16 mM total-N in combination with 0.3, 20, or 40 mM NaCl. The primary aim of the experiment was to provide insight into salinity tolerance and nutrient needs in the two ecotypes, thereby contributing to breeding of more resilient cultivars to salinity and nutrient stress. Nutritional qualities of the stamnagathi genotypes were also tested. The coastal-marine ecotype was more salt tolerant in terms of fresh shoot biomass production and contained significantly more water and macro- and micro-nutrients in the shoot per dry weight unit. The root Na+ concentration was markedly lower in the coastal-marine compared to the montane ecotype. The leaf Na+ concentration was similar in both ecotypes at external NaCl concentrations up to 20 mM, but significantly higher in the montane compared to the coastal-marine ecotype at 40 mM NaCl. However, the leaf Cl− concentration was consistently higher in the coastal-marine than in the montane ecotype within each salinity level. The marine ecotype also exhibited significantly less total phenols, carotenoids, flavonoids, and chlorophyll compared to the montane ecotype across all treatments. Integrating all findings, it appears that at moderate salinity levels (20 mM), the higher salt tolerance of the coastal-marine ecotype is associated with mechanisms mitigating Na+ and Cl− toxicity within the leaf tissues, such as salt dilution imposed through increased leaf succulence. Nevertheless, at high external NaCl levels, Na+ exclusion may also contribute to enhanced salt tolerance of stamnagathi. Both ecotypes exhibited a high N-use efficiency, as their shoot biomass was not restricted when the total-N supply varied from 16 to 4 mM. The leaf organic-N was not influenced by salinity, while the interaction ecotype × N-supply-level was insignificant, indicating that the mechanisms involved in the salt tolerance difference between the two ecotypes was not linked with N-acquisition or -assimilation within the plant. The current results indicate that both ecotypes are promising germplasm resources for future breeding programs.